Outcomes of Injection Laryngoplasty for Deep Interarytenoid Groove - Mothersole, Kelsey H.; Ulualp, Seckin O.; Johnson, Romaine F.; Brown, Ashley F.; Shah, Gopi B.; Liu, Christopher C.; Chorney, Stephen R. (International Archives of Otorhinolaryngology, 2023)
Introduction Deep interarytenoid groove (DIG) may cause swallowing dysfunction in children; however, the management of DIG has not been established.Objective We evaluated the subjective and objective outcomes of interarytenoid augmentation with injection in children with DIG.Methods Consecutive children under 18 years of age who underwent injection laryngoplasty for DIG were reviewed. Data pertaining to demographics, past medical history, past surgical history, and results of pre and postoperative video fluoroscopic swallow study (VFSS) were obtained. The primary outcome measure was the presence of thin liquid aspiration or penetration on postoperative VFSS. The secondary outcome measure was caregiver-reported improvement of symptoms.Results Twenty-seven patients had VFSS before and after interarytenoid augmentation with injection (IA). Twenty (70%) had thin liquid penetration and 12 (44%) had thin liquid aspiration before the IA. Thin liquid aspiration resolved in 9 children (45%) and persisted in 11 (55%). Of the 12 children who had thin liquid aspiration prior to IA, 6 (50%) had resolution of thin liquid aspiration after IA.Conclusions Injection laryngoplasty is a safe tool to improve swallowing function in children with DIG. Further studies are needed to assess the long-term outcomes of IA and identify predictors of successful IA in children with DIG.
Keywords: interarytenoid groove; injection laryngoplasty; children; dysphagia; endoscopic repair